Determinansi Kinerja Keuangan Pada Perusahaan Sektor Industri Dan Kimia Yang Terdaftar Di Bursa Efek Indonesia - Abdullah, Ikhsan; Lubis, Arnida Wahyuni (Lembaga Riset Ilmiah, 2022)
This study aims to determine the Determinants of Performance in Industrial and Chemical Sector Companies Listed on the Indonesia Textile Stock Exchange which are listed on the Indonesia Stock Exchange for the period 2018 - 2020. The determinants of Financial Performance in this study are Profitability, Solvency, and Activity. This type of research is quantitative research. The population of this study amounted to 78 companies. The sample selection used the purposive sampling method so that the sample studied consisted of 12 companies consisting of 2018 - 2020. The data analysis method used in this study was multiple linear regression. Based on the results of research conducted, it can be concluded that Profitability affects Financial Performance, Solvency hurts Financial Performance, and Activities have an effect on Financial Performance